INFERENCE STRATEGY TO IMPROVE THE STUDENTS’ LITERAL COMPREHENSION - Andi Asri Jumiati (Universitas Muhammadiyah Makassar, 2014)
The purpose of this research was to find out the improvement of the students’ comprehension in literal comprehension by using Inference Strategy at the second-year students’ of SMA YAPIP Sungguminasa Gowa. As has been stated in the previous chapter, the present research investigated the use of Inference Strategy to improve students’ reading comprehension in literal and interpretative comprehension. The research employed a pre-experimental design in SMA YAPIP Sungguminasa Gowa. Therefore, the findings and discussion in the previous chapter, the researcher conclude as Inference Strategy can improve the students’ reading comprehension in literal comprehension. It was proved by 74% of improvement which indicates that post-test value was higher than the pre-test while pre-test was 47, 73 and posttest 83, 22.Keywords: comprehension, literal, reading, inference strategy